2021
DOI: 10.3390/polym13132028
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-Robust Thermoconductive Films Made from Aramid Nanofiber and Boron Nitride Nanosheet for Thermal Management Application

Abstract: The development of highly thermally conductive composites with excellent electrical insulation has attracted extensive attention, which is of great significance to solve the increasingly severe heat concentration issue of electronic equipment. Herein, we report a new strategy to prepare boron nitride nanosheets (BNNSs) via an ion-assisted liquid-phase exfoliation method. Then, silver nanoparticle (AgNP) modified BNNS (BNNS@Ag) was obtained by in situ reduction properties. The exfoliation yield of BNNS was appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 81 publications
0
3
0
Order By: Relevance
“…In Fig. 3f, a comparison of the in-plane thermal conductivity of the composites with different BN filler contents is presented, 5,24,40–48 highlighting the excellent thermal conductivity performance achieved in this study. According to Fig.…”
Section: Resultsmentioning
confidence: 62%
“…In Fig. 3f, a comparison of the in-plane thermal conductivity of the composites with different BN filler contents is presented, 5,24,40–48 highlighting the excellent thermal conductivity performance achieved in this study. According to Fig.…”
Section: Resultsmentioning
confidence: 62%
“…Consequently, the original Kevlar fiber with a diameter of ~15 μm ( Figure 1 b) was dissociating into curly nanofibers with length in micrometer scale and diameter in the range of 20–30 nm, as revealed in the TEM image in Figure 1 c. Kotov et al found that the ANFs not only inherit the exceptional properties of Kevlar fiber, but also possess a large number of functional groups on their surface [ 17 ]. The nanoscale, high aspect ratio, surface activity, and good dispersibility of ANFs render them promising nanoscale building blocks to prepare advanced materials [ 1 , 22 , 23 , 28 ]. The Al 2 O 3 nanoplates, with a lateral size of approximately 1 μm and mean thickness of 100 nm ( Figure 1 d), were utilized to enhance the performance of ANFs based films, owing to their excellent dielectric properties [ 29 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Due to the physical entanglement and strong hydrogen bond interaction between nanofibers, ANFs have excellent mechanical strength and toughness [ 27 ]. ANFs began to be used to prepare multifunctional hybrid materials, including supercapacitors [ 28 , 29 , 30 ], sensors [ 31 , 32 ], thermal managers [ 8 , 18 , 33 , 34 ], infrared stealth materials [ 20 , 35 ], insulation materials [ 36 , 37 ], and electromagnetic interference shielding materials [ 38 ]. It is worth noting that aramid fiber, as one of the most heat-resistant organic materials, is widely used in heat insulation materials and engineering materials [ 19 , 39 ], but is easily ignitable in the absence of fire barriers [ 6 , 35 , 40 ].…”
Section: Introductionmentioning
confidence: 99%